PENGARUH KUALITAS PELAYANAN FRONTLINER, MOBILE BANKING DAN KEPERCAYAAN TERHADAP KEPUASAN NASABAH BANK SYARIAH INDONESIA DI KOTA MALANG - Riza Humayroh; Noor Shodiq Askandar; Afifudin Afifudin (El-Aswaq: Islamic Economics and Finance Journal, 2022)
This study aims to determine the partial and simultaneous effect of frontliner service quality, mobile banking and trust on customer satisfaction of Indonesian Islamic banks in the city of Malang. This research is a quantitative research. The method used to test the hypothesis is to use an instrument test, normality test, classical assumption test, multiple linear regression analysis and hypothesis testing with simultaneous test (F test), coefficient of determination (R2) and partial test (t test). The sample in this study was 92 respondents with the provisions, each respondent is a customer of an Indonesian Islamic bank and a customer who is a user of the mobile banking service application bsi mobile. The data used is primary data that can be obtained directly through questionnaires to Indonesian Islamic bank customers. The results showed that the quality of frontliner service, mobile banking and trust had an effect either partially or simultaneously on the satisfaction of Indonesian Islamic bank customers in the city of Malang. The results of the research on the hypothesis, show that the quality of frontliner service has a positive and significant effect on customer satisfaction, mobile banking has a positive and significant effect on customer satisfaction, and trust has a positive and significant effect on customer satisfaction.